2015
DOI: 10.1007/s00170-015-7632-y
|View full text |Cite
|
Sign up to set email alerts
|

Coated carbide tool failure analysis in high-speed intermittent cutting process based on finite element method

Abstract: Coated carbide tools are widely used in machining titanium alloys due to their excellent wear resistance, high strength, and hardness even at elevated temperature. The paper gives a special attention to the failure mechanisms of coated carbide cutting tools during high-speed intermittent cutting process. The effects of serrated chip formation on the instantaneous cutting forces, transient temperature, and thermal stress distributions on the cutting tool were investigated based on finite element method (FEM). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It was reported that thermal damage to the tools' material increased in proportion to mechanical damage as a result of the increasing cutting temperature in high-speed intermittent cutting process. 7,34 Tool failure analysis…”
Section: Effect Of Cutting Parameters On Tool Lifementioning
confidence: 99%
“…It was reported that thermal damage to the tools' material increased in proportion to mechanical damage as a result of the increasing cutting temperature in high-speed intermittent cutting process. 7,34 Tool failure analysis…”
Section: Effect Of Cutting Parameters On Tool Lifementioning
confidence: 99%
“…The stress variable rule on cutting tools was investigated to reveal the failure mechanisms based on FEM. 10 Moreover, the effects of key machining parameters on the cutting force and surface roughness were estimated based on FEM. [11][12][13][14] And both experimental and finite-element-based approaches were adopted to research the effect of coated textured tools on cutting performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ghani et al [18] found that the crack initiated and propagated at the cutting edge due to the effect of cyclic loading in intermittent milling titanium alloy. Wang et al [19] investigated the failure mechanisms of coated carbide tool in milling Ti-6Al-4V based on the finite element method and found that the tool failure mechanism was brittle fracture.…”
Section: Introductionmentioning
confidence: 99%